Image synthesis from a weakly calibrated image stereo pair - Dong, Yu Yu (2008)
This thesis proposes a new technique for image synthesis in perspective space. This means that with two reference images snapped by a weakly calibrated camera a third view in between two original ones can be generated. During the process, neither the 3-D geometry information of the same scene, nor camera information is needed. The key contribution in this thesis is the introduction of disparity interpolation to the perspective space. The disparity interpolation is based on the rectification process, by which two original reference views are transformed to what seem like images snapped by perspective cameras in parallel position. The feasibility of disparity interpolation of rectified images to synthesize a new image in perspective space is proven. To make sure continuous transition of synthesized image, the interpolation is naturally applied to de-rectification process.